Rapidly lethal dermatomyositis associated with cutaneous lymphangitis carcinomatosa - Resende, C (2013)
A 70-year-old woman with a recent diagnosis of dermatomyositis (DM) presented to the dermatology department for study of a probably paraneoplastic syndrome. On examination, we observed discrete, indurated, reddish, painful plaques and nodules on her abdomen and both thighs. A cutaneous biopsy from an abdominal nodule, performed as part of the paraneoplastic workup, was suggestive of cutaneous lymphangitis carcinomatosa, secondary to unknown malignancy. An extensive investigation to locate the site of the primary tumour revealed no specific findings. A course of palliative chemotherapy with cisplatin and 5-fluorouracil was then given, but the patient's condition deteriorated and 6 months after her initial observation the patient died. We describe this case because, to our knowledge, the association between DM and cutaneous lymphangitis carcinomatosa has not been described yet in the literature and to highlight that, DM can be a rapidly lethal disease.